Antibacterial Potential of the Ethyl Acetate Fraction of Ethanolic Extract of Kopasanda Leaves (Chromolaena odorata L.) Against Streptococcus Mutans - Ivan Junius Mesak; Mariana Kristiani (Griya Eka Sejahtera, 2026)
Background: Streptococcus mutans is the primary bacterium responsible for dental caries. Continuous use of synthetic antibacterial agents may cause side effects; therefore, natural antibacterial alternatives are needed. Kopasanda leaves (Chromolaena odorata L.) are known to contain bioactive compounds with potential antibacterial activity. This study aimed to evaluate the antibacterial activity of the ethyl acetate fraction of the ethanolic extract of kopasanda leaves (Chromolaena odorata L.) against Streptococcus mutans.Methods: An experimental laboratory study was conducted using the agar well diffusion method with ethyl acetate fractions at concentrations of 10%, 15%, and 20%. Gentamicin was used as the positive control and the solvent as the negative control. The inhibition zones were measured in millimeters and analyzed using One-Way ANOVA.Results: The ethyl acetate fraction showed antibacterial activity against Streptococcus mutans, with mean inhibition zone diameters of 11.33 mm, 13.49 mm, and 15.98 mm at concentrations of 10%, 15%, and 20%, respectively. The 20% concentration exhibited the highest antibacterial activity, and statistical analysis indicated a significant difference among treatments (p < 0.05).Conclusion: The ethyl acetate fraction of kopasanda leaf extract (Chromolaena odorata L.) exhibits antibacterial activity against Streptococcus mutans, with 20% being the most effective concentration.